Kinetics of martensite decomposition in the Cu-9Al-6Ag alloy - Adorno, A. T.; Silva, RAG (Elsevier B.V., 2005)
The non-occurrence of the beta' -> (alpha+ gamma(1)) decomposition reaction in the Cu-9 wt.% Al-6 wt.% Ag alloy, on ageing between 200 and 450 degrees C, is discussed considering the influence of Ag on point defects redistribution and energy difference between martensite and the ordered parent phase. (c) 2005 Elsevier B.V All rights reserved.
Keywords: metals; X-ray